Social systems for future manufacturing framework: An overarching view of people, organization and society - Muniz, Jorge [UNESP]; Zhang, Yufeng; Wintersberger, Daniel; Ramirez, Paulina (SAGE Publications, 2024)
Drawing on insights from relevant scholarship in the areas of producing engineering, sociology of work and political economy, as well as a series of ‘webinars’ with R&D managers, production managers and trade union representatives conducted between 2021 and 22, we propose an interdisciplinary, multidimensional framework (‘social systems for future manufacturing’) as a means to better understand the shopfloor and societal implications of technological change in the context of the ‘fourth industrial revolution’. Our framework entails three distinct though interrelated levels of analysis (worker, manufacturing, as well as societal), all of which are necessary to engage with in order to understand the implications of digital transformation. We argue that the extent to which employee voice is institutionally embedded at societal level, will have an impact on the way in which new technology will be developed and implemented (namely in a labour-saving or labouraugmenting way). We also discuss relevant factors in terms of workforce skills development at individual and firm level, as well as in terms of national vocational training and development infrastructure, and how these are likely to determine industrial competitiveness in the context of the fourth industrial revolution. Theoretical and managerial implications around work organisation and workforce training are discussed.
Keywords: digital transformation; Future manufacturing; Industry 4.0/5.0; innovation systems; learning processes; management; skills; social systems